Lipoprotein N-terminal modification in Bacillus: a new paradigm for extracellular acetylation and species-dependent Toll-like receptor 2 immunomodulation - Gloria Komazin; Rachel M. Wigmore; Aditi M. Ranade; Amena A. Rizk; John H. Gardiner; Timothy C. Meredith (mBio)
ABSTRACT Lipoproteins are a defining feature of extracellular bacterial membrane surfaces. Acylation of an invariant N-terminal cysteine residue tethers proteins to the cell surface, where they participate in many cellular processes occurring at the membrane-environment interface. Lipoproteins also double as key ligands for bacterial detection by the mammalian innate immune system, which when bound by Toll-like receptor 2 (TLR2) complexes orchestrate a pro-inflammatory response to clear infections. While nearly all bacteria synthesize lipoproteins, variable acylation states can attenuate TLR2 signaling. In Bacillus subtilis, lipoproteins are N-acetylated to form acetylated lipoproteins (Ac-LP) after being transported across the membrane. How high-energy acetyl donors are shuttled to the cell surface for trasnfer is unknown. Using a transposon-based genetic screen to identify mutants with altered TLR2 activation and in vitro reconstitution of the enzyme machinery, we now describe an acetylated heptaprenylglyceryl (Ac-HepG) carrier synthesized by PcrB/YvoF in the cytosol that is required for lipoprotein acetylation. We propose Ac-HepG is shuttled to the outer membrane leaflet for use by the previously uncharacterized integral membrane protein, lipoprotein heptaprenylglyceryl N-acetyl transferase (LhaT) (formerly YpjA), for N-acetylation of the α-amino termini of lipoprotein substrates. We provide evidence that LhaT, which in most Bacillus spp. makes the high-affinity Ac-LP TLR2 ligand, has become pseudogenized in the Bacillus cereus group subclade that harbors opportunistic pathogens. A naturally occurring poly-tyrosine insertion within LhaT from Bacillus anthracis isolates prevents acetyl transfer, allowing the flanking lipoprotein remodeling gene lit to quantitatively convert the population to the TLR2-silent lyso-lipoprotein (lyso-LP) chemotype.IMPORTANCEProtein acetylation is an important and widespread post-translational modification. Annotation of LhaT and the lipoprotein N-acetylation pathway provides a paradigm for how cells can source high-energy extracellular acetyl donors, with the enigmatic lipid Ac-HepG now joining the cytosolic acetyl-coenzyme A and acetyl-phosphate as acetyl group donors. While Ac-LP biosynthetic pathway genes appear to be universally conserved in all Bacillus spp., those associated with pathogenic lineages have often lost function. In B. anthracis strains, LhaT has been inactivated by insertion of poly-tyrosine runs of variable length that favors chemotype conversion to lyso-LP and evasion of TLR2 detection. Lipoprotein chemotypes are thus critical determinants governing environmental and pathogen differentiation among Bacillus spp.